Venom system variation and the division of labor in the colonial hydrozoan Hydractinia symbiolongicarpus. (June 2022) - Klompen, Anna M.L.; Sanders, Steven M.; Cartwright, Paulyn
Abstract: Cnidarians (jellyfish, hydroids, sea anemones, and corals) possess a unique method for venom production, maintenance, and deployment through a decentralized system composed of different types of venom-filled stinging structures called nematocysts. In many species, nematocyst types are distributed heterogeneously across functionally distinct tissues. This has led to a prediction that different nematocyst types contain specific venom components. The colonial hydrozoan, Hydractinia symbiolongicarpus, is an ideal system to study the functional distribution of nematocyst types and their venoms, given that they display a division of labor through functionally distinct polyps within the colony. Here, we characterized the composition and distribution of nematocysts (cnidome) in the different polyp types and show that the feeding polyp (gastrozooid) has a distinct cnidome compared to the reproductive (gonozooid) and predatory polyp (dactylozooid). We generated a nematocyst-specific reporter line to track nematocyst development (nematogenesis) in H. symbiolongicarpus, and were able to confirm that nematogenesis primarily occurs in the mid-region of the gastrozooid and throughout stolons (tubes of epithelia that connect the polyps in the colony). This reporter line enabled us to isolate a nematocyst-specific lineage of cells for de novo transcriptome assembly, annotate venom-like genes (VLGs) and determine differential expression (DE) across polyp types. We show that a majority of VLGs are upregulated in gastrozooids, consistent with it being the primary site of active nematogenesis. However, despite gastrozooids producing more nematocysts, we found a number of VLGs significantly upregulated in dactylozooids, suggesting that these VLGs may be important for prey-capture. Our transgenic Hydractinia reporter line provides an opportunity to explore the complex interplay between venom composition, nematocyst diversity, and ecological partitioning in a colonial hydrozoan that displays a division of labor. Graphical abstract: Image 1 Highlights: Functionally specific polyp types in Hydractinia symbiolongicarpus have distinct cnidomes. We present a nematocyst-targeted transgenic line for H. symbiolongicarpus, showcasing active areas of nematogenesis. 105 venom-like genes (VLGs) were annotated from an assembled nematocyst-enriched transcriptome. Several VLGs were significantly upregulated in feeding polyps, consistent with being a site of active nematogenesis. Differential expression analysis suggests that different polyp types express distinct combinations of VLGs.